Mortality Associated with Phaeochromocytoma - Prejbisz, A.; Lenders, J.W. M.; Eisenhofer, G.; Januszewicz, A. (Hormone and Metabolic Research, 2013)
Two major categories of mortality are distinguished in patients with phaeochromocytoma. First, the effects of excessive circulating catecholamines may result in lethal complications if the disease is not diagnosed and/or treated timely. The second category of mortality is related to development of metastatic disease or other neoplasms. Improvements in disease recognition and diagnosis over the past few decades have reduced mortality from undiagnosed tumours. Nevertheless, many tumours remain unrecognised until they cause severe complications. Death resulting from unrecognised or untreated tumour is caused by cardiovascular complications. There are also numerous drugs and diagnostic or therapeutic manipulations that can cause fatal complications in patients with phaeochromocytoma. Previously it has been reported that operative mortality was as high as 50% in unprepared patients with phaeochromocytoma who were operated and in whom the diagnosis was unsuspected. Today mortality during surgery in medically prepared patients with the tumour is minimal. Phaeochromocytomas may be malignant at presentation or metastases may develop later, but both scenarios are associated with a potentially lethal outcome. Patients with phaeochromocytoma run an increased risk to develop other tumours, resulting in an increased mortality risk compared to the general population. Phaeochromocytoma during pregnancy represents a condition with potentially high maternal and foetal mortality. However, today phaeochromocytoma in pregnancy is recognised earlier and in conjunction with improved medical management, maternal mortality has decreased to less than 5%.
Keywords: death; cardiovascular complications; malignancy; pregnancy; multisystem crisis